The Eurasian heartland: a continental perspective on Y-chromosome diversity. - Wells, R; Yuldasheva, N; Ruzibakiev, R; Underhill, P; Evseeva, I; Blue-Smith, J; Jin, L; Su, B; Pitchappan, R; Shanmugalakshmi, S; Balakrishnan, K; Read, M; et al. (2001)
The nonrecombining portion of the human Y chromosome has proven to be a valuable tool for the study of population history. The maintenance of extended haplotypes characteristic of particular geographic regions, despite extensive admixture, allows complex demographic events to be deconstructed. In this study we report the frequencies of 23 Y-chromosome biallelic polymorphism haplotypes in 1,935 men from 49 Eurasian populations, with a particular focus on Central Asia. These haplotypes reveal traces of historical migrations, and provide an insight into the earliest patterns of settlement of anatomically modern humans on the Eurasian continent. Central Asia is revealed to be an important reservoir of genetic diversity, and the source of at least three major waves of migration leading into Europe, the Americas, and India. The genetic results are interpreted in the context of Eurasian linguistic patterns.